SMART SALARY MANAGEMENT SAVING AND INVESTMENT STRATEGIES FOR THE FUTURE - Mahfirah, Titis Fatarina; Ahmad, Gatot Nazir; Widyastuti, Umi; Wastuti, Wahyu; Pahala, Indra (International Journal of Engagement and Empowerment (IJE2), 2025)
This community service program aims to enhance the financial literacy and investment awareness of Indonesian Migrant Workers (PMI) in Tainan, Taiwan. Many PMIs face financial challenges after returning home due to limited financial knowledge and lack of long-term savings strategies. The program conducted by the Faculty of Economics and Business, Universitas Negeri Jakarta, implemented structured activities including socialization, digital financial literacy training, financial planning workshops, and basic investment training. The training introduced digital tools such as the Livin’ by Mandiri application to encourage systematic saving and responsible investment behavior. Evaluation results from 15 participants showed an average post-training score of 60.57, indicating improved understanding and application of financial management concepts. The program not only strengthened participants’ financial capabilities but also fostered independence, self-confidence, and solidarity among PMIs. These outcomes contribute to achieving Sustainable Development Goals (SDG) 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth), promoting sustainable financial well-being for migrant workers abroad.